Method for preparing foamed ceramic based on high-calcium low-silicon household garbage incineration fly ash
By washing and mixing the fly ash incineration of high calcium and low silicon domestic waste, high-strength foam ceramics were prepared, which solved the problems of low fly ash treatment strength and heavy metal pollution in the existing technology, and achieved harmless treatment and Resource utilization.
Patent Information
- Application Number
- CN202411437001.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The existing methods for incineration of domestic waste have problems such as low strength and heavy metal ion leaching concentrations that do not meet national standards, resulting in land pollution.
By washing the fly ash with high calcium and low silicon type domestic waste, reducing the chloride ion content, mixing it with kaolin, quartz or waste glass powder, adding silicon carbide as a foaming agent, and after ball milling and sintering, a high bending strength is prepared. And the foam ceramics with heavy metal ion leaching concentration meet national standards.
The high strength of foam ceramics and the leaching concentration of heavy metal ions are achieved in accordance with national standards, and provide harmless treatment and resource utilization methods for domestic waste incineration fly ash.
Smart Images

Figure CN119306473A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of harmless treatment and resource utilization of domestic waste incineration fly ash, and particularly relates to a method for preparing foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash. Background Art
[0002] With the continuous improvement of human material living standards, the scale of fly ash generated by the incineration of domestic waste has expanded dramatically. The current mainstream fly ash treatment method is to directly landfill the solidified or stabilized fly ash. This treatment method is simple and fast, but it has the problem of occupying land resources. At the same time, there are also a small amount of toxic substances such as dioxins and heavy metals in the fly ash, which may cause secondary pollution to the land. Therefore, it is urgent to research and develop green and environmentally friendly fly ash harmless treatment technology.
[0003] Foam ceramic is a green and environmentally friendly high-porosity ceramic material with the characteristics of low bulk density, large specific surface area, strong sound insulation and heat preservation ability, and low dielectric constant. Its raw material components are mainly concentrated in the SiO2-Al2O3-RO-R2O system (RO is an alkaline earth metal oxide, and R2O is an alkali metal oxide). The main components of fly ash are CaO, SiO2, and Al2O3, which belong to the CaO-SiO2-Al2O3 system and can be used as a raw material for producing foam ceramics. Although there are methods for preparing foam ceramic materials using fly ash from the incineration of domestic waste, the foam ceramic materials prepared by these methods generally have the problem of low strength. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for preparing foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash. The foam ceramics prepared by the method of the present invention have a heavy metal ion leaching concentration that meets the national standard requirements and a flexural strength that far exceeds the national standard requirements.
[0005] The technical solution of the present invention:
[0006] The method for preparing foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0007] (1) Washing high-calcium, low-silicon domestic waste incineration fly ash with water to reduce the chloride ion content; the high-calcium, low-silicon domestic waste incineration fly ash contains 30wt% to 45wt% CaO and 15wt% to 25wt% SiO2.
[0008] (2) Washed fly ash, kaolin and quartz or waste glass powder are used as raw materials, silicon carbide is used as a foaming agent, and they are added into a rapid grinding machine for ball milling. After the ball milling is completed, the mixture is dried and sieved to prepare a mixed material.
[0009] (3) Weighing the required amount of the mixed material for tableting, placing a corundum pad, heating and sintering in a resistance furnace according to a prescribed firing system to obtain foam ceramics. The mixed material contains the following components: 40wt% to 60wt% SiO2, 10wt% to 25wt% Al2O3, 10wt% to 20wt% CaO, and 0.2wt% to 1.0wt% silicon carbide.
[0010] Preferably, the particle size of the raw materials does not exceed 100 mesh, the particle size of silicon carbide is ≤30 μm, and the mixed material is ball-milled and dried, and then sieved through a 100 mesh sieve.
[0011] Preferably, the high-calcium and low-silicon domestic waste incineration fly ash comes from Guangdong. The main chemical components of the domestic waste incineration fly ash in Guangdong are: CaO content of 30wt% ~ 35wt%, SiO2 content of 20wt% ~ 25wt%, Al2O3 content of 10wt% ~ 15wt%, SO3 content of 10wt% ~ 15wt%, Fe2O3 content of 5wt% ~ 10wt%, MgO content of 5wt% ~ 10wt%, TiO2 content of 1wt% ~ 2wt%, K2O content of 1wt% ~ 2wt%, P2O5 content of 0.5wt% ~ 1.5wt%, MnO content of 0.1wt% ~ 0.5wt%, and the remainder is impurities, totaling 100%.
[0012] Preferably, the high-calcium and low-silicon domestic waste incineration fly ash comes from Guangxi. The main chemical components of the domestic waste incineration fly ash in Guangxi are: CaO content of 40wt% ~ 45wt%, SiO2 content of 15wt% ~ 20wt%, SO3 content of 10wt% ~ 15wt%, Al2O3 content of 5wt% ~ 10wt%, MgO content of 5wt% ~ 10wt%, Fe2O3 content of 1wt% ~ 5wt%, TiO2 content of 1wt% ~ 2wt%, P2O5 content of 1wt% ~ 2wt%, K2O content of 0.1wt% ~ 1wt%, MnO content of 0.1wt% ~ 0.5wt%, and the remainder is impurities, totaling 100%.
[0013] Preferably, kaolin consists of the following components: SiO2 content of 55wt% to 60wt%, Al2O3 content of 40wt% to 45wt%, Fe2O3 content of 0.1wt% to 1wt%, K2O content of 0.1wt% to 1wt%, TiO2 content of 0.01wt% to 0.1wt%, BaO content of 0.01wt% to 0.1wt%, MnO content of 0.01wt% to 0.1wt%, SO3 content of 0.01wt% to 0.1wt%, and the remainder is impurities, totaling 100%.
[0014] Preferably, quartz consists of the following components: SiO2 content is 99.00wt%~99.80wt%, Al2O3 content is 0.1wt%~1wt%, Fe2O3 content is 0.01wt%~0.1wt%, CaO content is 0.01wt%~0.1wt%, SO3 content is 0.01wt%~0.1wt%, totaling 100%.
[0015] Preferably, the waste glass powder is composed of the following components: SiO2 content is 90wt%~95wt%, Na2O content is 5wt%~10wt%, Al2O3 content is 1wt%~5wt%, CaO content is 0.1wt%~0.5wt%, K2O content is 0.1wt%~0.5wt%, P2O5 content is 0.1wt%~0.5wt%, SO3 content is 0.1wt%~0.5wt%, Fe2O3 content is 0.01wt%~0.1wt%, TiO2 content is 0.01wt%~0.1wt%, and the remainder is impurities, totaling 100%.
[0016] Preferably, Guangdong fly ash or Guangxi fly ash, kaolin and quartz or waste glass powder are used as raw materials, and silicon carbide is used as a foaming agent to prepare high-strength foam ceramics. A microcomputer-controlled electronic universal testing machine is used, and the bending strength is tested and compared with reference to [national standard] GBT6569-2006 "Test method for bending strength of fine ceramics" and [national standard] JCT647-2005 "Foam ceramic insulation products", the sample size is 3*4*40mm, the loading speed is 0.5mm / min, and the span is 30mm; the Archimedes drainage method is used to test its various physical properties; the flame atomic absorption spectrophotometer method is used, and the heavy metal leaching concentration is tested with reference to [national standard] HJ1222-2021 "Solid waste-Determination of moisture and dry matter content-Gravimetric method" and HJT766-2015 "Solid waste-Leaching toxicity leaching method-sulfuric acid and nitric acid method".
[0017] Preferably, in step (1), the fly ash is pretreated, the liquid-to-solid ratio of deionized water to fly ash is 2.5:1, magnetic stirring is performed for 30-60 minutes, and the washed fly ash is dried at 105° C. for 12 hours.
[0018] Preferably, in step (2), washed Guangdong fly ash or Guangxi fly ash, kaolin, quartz or waste glass powder are mixed in a ratio of 2:2:1, a foaming agent silicon carbide is added, and the mixture is ball-milled in a fast grinder for 8 hours (the ball-to-water ratio is 2:1:0.8), and the ball-milled mixture is dried at 105°C for 12 hours and sieved through 100 mesh. The particle size of the raw materials does not exceed 100 mesh, and the particle size of silicon carbide is ≤30 μm.
[0019] Preferably, in step (3), the mixed material is pressed into tablets and then the foam ceramic is sintered according to a prescribed firing system (① using Guangdong fly ash as raw material: heating from room temperature to 1230°C-1250°C, heating rate of 2°C / min-4°C / min, keeping warm for 20min-60min, and then cooling; ② using Guangxi fly ash as raw material: heating from room temperature to 1145°C-1155°C, heating rate of 2°C / min-4°C / min, keeping warm for 20min-60min, and then cooling).
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The invention firstly pre-treats high-calcium and low-silicon domestic waste incineration fly ash, and reduces the chloride ion content thereof through a water washing process; then, the high-calcium and low-silicon domestic waste incineration fly ash, kaolin and quartz or waste glass powder are mixed so that the effective components in the mixture match the effective components of foam ceramics, silicon carbide is used as a foaming agent, and the mixture is ball-milled, wherein the mixture contains the following components: 40wt% to 60wt% of SiO2, 10wt% to 25wt% of Al2O3, 10wt% to 20wt% of CaO, and 0.2wt% to 1.0wt% of silicon carbide; finally, the foam ceramics are sintered at a high temperature according to a prescribed sintering system, and during the sintering process, the fixation of heavy metal ions is achieved, the leaching concentration of heavy metal ions is reduced, and at the same time, the material has a pore structure and the strength is improved. The heavy metal ion leaching concentration of the prepared foam ceramic material meets the national standard requirements, and the flexural strength far exceeds the national standard requirements. It can be used for sound insulation, heat preservation, structural construction, etc., which not only realizes waste utilization and provides a new way for the harmless treatment of fly ash from the incineration of domestic waste, but also turns waste into treasure and broadens the application of fly ash from the incineration of domestic waste. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The XRD spectra and physical images of Guangdong fly ash, Guangxi fly ash, kaolin, quartz, and waste glass powder in Example 1 and Example 10; (a1) Guangdong fly ash; (a2) Guangxi fly ash; (b) kaolin; (c1) quartz; (c2) waste glass powder.
[0023] Figure 2 The XRD spectra and physical images of the mixed materials and foam ceramics in Example 1 and Example 10, wherein (d1) contains the mixed material of Guangdong fly ash; (d2) contains the mixed material of Guangxi fly ash; (e1) contains the foam ceramics of Guangdong fly ash; and (e2) contains the foam ceramics of Guangxi fly ash.
[0024] Figure 3 These are SEM images and pore size distribution diagrams of different regions of the Guangdong fly ash-containing foam ceramics in Example 1, where (a), (b), (c) and (d) are SEM images of different positions, respectively, and (e) is a pore size distribution diagram.
[0025] Figure 4 These are the SEM images and pore size distribution diagrams of different areas of the foam ceramics containing Guangxi fly ash in Example 10: (a), (b), (c) and (d) are SEM images of different positions, respectively, and (e) is a pore size distribution diagram.
[0026] Figure 5 In the figure, (a) is the SEM image of the foam ceramic containing Guangdong fly ash in Example 1, (b) is the EDS spectrum of the foam ceramic containing Guangdong fly ash in Example 1, and (c) is the distribution diagram of each element in (a).
[0027] Figure 6 In the figure, (a) is the EDS spectrum of the foam ceramic containing Guangxi fly ash in Example 10, (b) is the EDS spectrum of the foam ceramic containing Guangxi fly ash in Example 10, and (c) is the distribution diagram of each element in (a).
[0028] Figure 7 In the figure, (a) is a physical picture of the foam glass of comparative example 1, and (b) is a physical picture of the cross section of the foam glass of comparative example 1.
[0029] Figure 8 (a) is the actual foam ceramic of the incomplete sintering of Comparative Example 2 Figure 1 , (b) is the actual foam ceramic of the incomplete sintering of Comparative Example 2 Figure 2 .
[0030] Fig. 9 (a) is the actual glass ceramic of Comparative Example 3 Figure 1 , (b) is the actual glass ceramic of Comparative Example 3 Figure 2 .
[0031] Fig.10 In the figure, (a) is a physical picture of the foam ceramic of comparative example 4, and (b) is a physical picture of the cross section of the foam ceramic of comparative example 4. DETAILED DESCRIPTION
[0032] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention. The experimental methods and detection methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.
[0033] After testing, the Guangdong domestic waste incineration fly ash used in the following embodiments specifically contains the following components: CaO content is 33.04wt%, SiO2 content is 23.72wt%, SO3 content is 12.57wt%, Al2O3 content is 12.34wt%, Fe2O3 content is 7.51wt%, MgO content is 5.86wt%, TiO2 content is 1.66wt%, K2O content is 1.19wt%, P2O5 content is 0.98wt%, MnO content is 0.19wt%, and the remainder is impurities, totaling 100%.
[0034] The fly ash from the incineration of domestic waste in Guangxi contains the following components: CaO content is 44.24wt%, SiO2 content is 16.92wt%, SO3 content is 13.67wt%, MgO content is 8.59wt%, Al2O3 content is 7.26wt%, Fe2O3 content is 4.18wt%, TiO2 content is 1.33wt%, P2O5 content is 1.18wt%, K2O content is 0.77wt%, MnO content is 0.18wt%, and the remainder is impurities, totaling 100%.
[0035] Kaolin contains the following components: SiO2 content is 57.50wt%, Al2O3 content is 40.97wt%, Fe2O3 content is 0.71wt%, K2O content is 0.60wt%, SO3 content is 0.06wt%, BaO content is 0.05wt%, TiO2 content is 0.04wt%, MnO content is 0.03wt%, CuO content is 0.02wt%, and Zr2O content is 0.02wt%.
[0036] The quartz contains the following components: SiO2 content is 99.24wt%, Al2O3 content is 0.72wt%, SO3 content is 0.02wt%, Fe2O3 content is 0.01wt%, and CaO content is 0.01wt%.
[0037] The waste glass powder contains the following components: SiO2 content is 90.90wt%, Na2O content is 5.40wt%, Al2O3 content is 2.71wt%, CaO content is 0.24wt%, SO3 content is 0.20wt%, P2O5 content is 0.17wt%, Zr2O content is 0.13wt%, K2O content is 0.10wt%, Fe2O3 content is 0.08wt%, CuO content is 0.04wt%, and TiO2 content is 0.03wt%.
[0038] Foam ceramic is a green and environmentally friendly ceramic material with high porosity. Its raw material components are mainly concentrated in the SiO2-Al2O3-RO-R2O system (RO is alkaline earth metal oxide, R2O is alkali metal oxide); the main components of fly ash are CaO, SiO2, Al2O3, belonging to the CaO-SiO2-Al2O3 system, which can be used as the raw material for producing foam ceramic. Among them, SiO2 plays a skeleton role. Too much will increase the sintering temperature. The content should be moderate and controlled at 40wt% to 60wt%; Al2O3 has the function of enhancing mechanical strength and stabilizing bubble structure. Too high will increase the softening temperature of raw materials. The content is controlled at 10wt% to 25wt%; CaO can improve material properties and act as a sintering aid, but excessive amount is not conducive to pore formation. The content is controlled at 10wt% to 20wt%; SiC is a foaming agent, and the content is controlled at 0.2wt% to 1wt%.
[0039] The present invention will be specifically described below by means of the following examples and comparative examples.
[0040] Example 1
[0041] In this embodiment, a method for preparing high-strength foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0042] (1) First, the waste incineration fly ash in Guangdong was pretreated by washing to reduce its chloride ion content. In the experiment, 100g of dry waste incineration fly ash and 250ml of deionized water were weighed and added to a 500ml beaker (liquid-solid ratio of 2.5:1). A magnetic rotor was added and magnetic stirring was performed for 30min. The solid-liquid separation was performed using "qualitative filter paper + sand core filter device + vacuum pump". Deionized water was added and filtered until the filtrate was pure. The filtrate was then dried and weighed (dried at 105℃ for 12h). EDX was used to detect the content of each element in the fly ash before and after washing to verify the removal effect of chloride ions (ideal effect: the chloride ion content in the fly ash after washing is less than 0.1%).
[0043] (2) Then the washed Guangdong fly ash, kaolin and quartz are mixed in a ratio of 2:2:1, and an appropriate amount of foaming agent silicon carbide is added to form a mixture; in the mixture, the content of SiO2 is 51.81wt%, the content of Al2O3 is 21.25wt%, the content of CaO is 13.09wt%, the content of SO3 is 5.01wt%, the content of Fe2O3 is 3.26wt%, the content of MgO is 2.32wt%, the content of SiC is 1wt%, the content of K2O is 0.71wt%, the content of TiO2 is 0.67wt%, the content of P2O5 is 0.39wt%, the content of MnO is 0.08wt%, and the remainder is impurities, totaling 100%; ball milling is carried out in a fast grinding mill for 8h (the ball-to-water ratio is 2:1:0.8), and after ball milling, it is dried at 105°C for 12h and sieved through 100 mesh.
[0044] (3) Finally, the required amount of the mixture is weighed and pressed into a sheet (from 10 MPa until the pressure no longer decreases), and a corundum pad is placed on the sheet. The sheet is sintered in a resistance furnace according to the specified firing schedule (heating from room temperature to 1230°C at a heating rate of 3°C / min, keeping the temperature for 40 min, and then cooling) to obtain a foam ceramic product.
[0045] With reference to [national standard] GBT6569-2006 "Test method for bending strength of fine ceramics" and [national standard] JCT647-2005 "Foam ceramic insulation products", a microcomputer-controlled electronic universal testing machine was used with a sample size of 3*4*40mm, a loading speed of 0.5mm / min, and a span of 30mm to test and compare its bending strength.
[0046] Referring to [national standard] GBT1966-1996 "Test method for apparent porosity and bulk density of porous ceramics", [national standard] HJ1222-2021 "Solid waste-Determination of moisture and dry matter content-Gravimetric method", and HJT766-2015 "Solid waste-Leaching toxicity leaching method-sulfuric acid and nitric acid method", the Archimedes drainage method was used to test its various physical properties, and the flame atomic absorption spectrophotometer method was used to test its heavy metal leaching concentration. The results are shown in Table 1:
[0047] Table 1 Physical properties, flexural strength and heavy metal ion leaching concentration of foam ceramics
[0048]
[0049] Example 2
[0050] In this embodiment, a method for preparing high-strength foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0051] (1) First, the waste incineration fly ash in Guangdong was pretreated by washing to reduce its chloride ion content. In the experiment, 100g of dry waste incineration fly ash and 250ml of deionized water were weighed and added to a 500ml beaker (liquid-solid ratio of 2.5:1). A magnetic rotor was added and magnetic stirring was performed for 30min. The solid-liquid separation was performed using "qualitative filter paper + sand core filter device + vacuum pump". Deionized water was added and filtered until the filtrate was pure. The filtrate was then dried and weighed (dried at 105℃ for 12h). EDX was used to detect the content of each element in the fly ash before and after washing to verify the removal effect of chloride ions (ideal effect: the chloride ion content in the fly ash after washing is less than 0.1%).
[0052] (2) Then the washed Guangdong fly ash, kaolin and quartz are mixed in a ratio of 2:2:1, and an appropriate amount of foaming agent silicon carbide is added to form a mixture; in the mixture, the content of SiO2 is 51.81wt%, the content of Al2O3 is 21.25wt%, the content of CaO is 13.09wt%, the content of SO3 is 5.01wt%, the content of Fe2O3 is 3.26wt%, the content of MgO is 2.32wt%, the content of SiC is 1wt%, the content of K2O is 0.71wt%, the content of TiO2 is 0.67wt%, the content of P2O5 is 0.39wt%, the content of MnO is 0.08wt%, and the remainder is impurities, totaling 100%; ball milling is carried out in a fast grinding mill for 8h (the ball-to-water ratio is 2:1:0.8), and after ball milling, it is dried at 105°C for 12h and sieved through 100 mesh.
[0053] (3) Finally, the required amount of the mixed material is weighed and pressed into a sheet (from 10 MPa until the pressure no longer decreases), and a corundum pad is placed on the sheet. The sheet is sintered in a resistance furnace according to the specified firing schedule (heating from room temperature to 1230°C at a heating rate of 2°C / min, keeping the temperature for 20 min, and then cooling) to obtain a foam ceramic product.
[0054] With reference to [national standard] GBT6569-2006 "Test method for bending strength of fine ceramics" and [national standard] JCT647-2005 "Foam ceramic insulation products", a microcomputer-controlled electronic universal testing machine was used with a sample size of 3*4*40mm, a loading speed of 0.5mm / min, and a span of 30mm to test and compare its bending strength.
[0055] Referring to [national standard] GBT1966-1996 "Test method for apparent porosity and bulk density of porous ceramics", the Archimedes drainage method was used to test its various physical properties. The results are shown in Table 2:
[0056] Table 2 Physical properties and flexural strength of foam ceramics
[0057]
[0058] Example 3
[0059] In this embodiment, a method for preparing high-strength foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0060] Except for the sintering system in step (3) (heating from room temperature to 1250° C., heating rate of 3° C. / min, keeping temperature for 60 min, and then cooling), the remaining steps are the same as those in Example 2. The results are shown in Table 3:
[0061] Table 3 Physical properties and flexural strength of foam ceramics
[0062]
[0063] Example 4
[0064] In this embodiment, a method for preparing high-strength foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0065] (1) First, the waste incineration fly ash in Guangdong was pretreated by washing to reduce its chloride ion content. In the experiment, 100g of dry waste incineration fly ash and 250ml of deionized water were weighed and added to a 500ml beaker (liquid-solid ratio of 2.5:1). A magnetic rotor was added and magnetic stirring was performed for 30min. The solid-liquid separation was performed using "qualitative filter paper + sand core filter device + vacuum pump". Deionized water was added and filtered until the filtrate was pure. The filtrate was then dried and weighed (dried at 105℃ for 12h). EDX was used to detect the content of each element in the fly ash before and after washing to verify the removal effect of chloride ions (ideal effect: the chloride ion content in the fly ash after washing is less than 0.1%).
[0066] (2) Then the washed Guangdong fly ash, kaolin and quartz are mixed in a ratio of 2:2:1, and an appropriate amount of foaming agent silicon carbide is added to form a mixture; in the mixture, the content of SiO2 is 52.07wt%, the content of Al2O3 is 21.36wt%, the content of CaO is 13.15wt%, the content of SO3 is 5.03wt%, the content of Fe2O3 is 3.27wt%, the content of MgO is 2.33wt%, the content of K2O is 0.71wt%, the content of TiO2 is 0.68wt%, the content of SiC is 0.5wt%, the content of P2O5 is 0.39wt%, the content of MnO is 0.08wt%, and the remainder is impurities, totaling 100%; ball milling is carried out in a fast grinding mill for 8h (the ball-to-water ratio is 2:1:0.8), and after ball milling, it is dried at 105°C for 12h and sieved through 100 mesh.
[0067] (3) Finally, the required amount of the mixed material is weighed and pressed into a sheet (from 10 MPa until the pressure no longer decreases), and a corundum pad is placed on the sheet. The sheet is sintered in a resistance furnace according to the specified firing schedule (heating from room temperature to 1240°C at a heating rate of 4°C / min, keeping the temperature for 40 min, and then cooling) to obtain a foam ceramic product.
[0068] The detection method is the same as in Example 2, and the results are shown in Table 4:
[0069] Table 4 Physical properties and flexural strength of foam ceramics
[0070]
[0071] Example 5
[0072] In this embodiment, a method for preparing high-strength foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0073] Except for (3) the sintering system (heating from room temperature to 1240° C., heating rate of 2° C. / min, keeping temperature for 60 min, and then cooling), the remaining steps are the same as those in Example 4. The results are shown in Table 5:
[0074] Table 5 Physical properties and flexural strength of foam ceramics
[0075]
[0076] Example 6
[0077] In this embodiment, a method for preparing high-strength foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0078] Except for (3) the sintering system (heating from room temperature to 1250° C., heating rate of 4° C. / min, keeping at this temperature for 20 min, and then cooling), the remaining steps are the same as those in Example 4. The results are shown in Table 6:
[0079] Table 6 Physical properties and flexural strength of foam ceramics
[0080]
[0081] Example 7
[0082] In this embodiment, a method for preparing high-strength foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0083] (1) First, the waste incineration fly ash in Guangdong was pretreated by washing to reduce its chloride ion content. In the experiment, 100g of dry waste incineration fly ash and 250ml of deionized water were weighed and added to a 500ml beaker (liquid-solid ratio of 2.5:1). A magnetic rotor was added and magnetic stirring was performed for 30min. The solid-liquid separation was performed using "qualitative filter paper + sand core filter device + vacuum pump". Deionized water was added and filtered until the filtrate was pure. The filtrate was then dried and weighed (dried at 105℃ for 12h). EDX was used to detect the content of each element in the fly ash before and after washing to verify the removal effect of chloride ions (ideal effect: the chloride ion content in the fly ash after washing is less than 0.1%).
[0084] (2) Then the washed Guangdong fly ash, kaolin and quartz are mixed in a ratio of 2:2:1, and an appropriate amount of foaming agent silicon carbide is added to form a mixture; in the mixture, the content of SiO2 is 52.23wt%, the content of Al2O3 is 21.42wt%, the content of CaO is 13.19wt%, the content of SO3 is 5.05wt%, the content of Fe2O3 is 3.28wt%, the content of MgO is 2.34wt%, the content of K2O is 0.71wt%, the content of TiO2 is 0.68wt%, the content of P2O5 is 0.39wt%, the content of SiC is 0.2wt%, the content of MnO is 0.08wt%, and the remainder is impurities, totaling 100%; ball milling is carried out in a fast grinding mill for 8h (the ball-to-water ratio is 2:1:0.8), and after ball milling, it is dried at 105°C for 12h and sieved through 100 mesh.
[0085] (3) Finally, the required amount of the mixed material is weighed and pressed into a sheet (from 10 MPa until the pressure no longer decreases), and a corundum pad is placed on the sheet. The sheet is sintered in a resistance furnace according to the specified firing schedule (heating from room temperature to 1230°C at a heating rate of 4°C / min, keeping the temperature for 60 min, and then cooling) to obtain a foam ceramic product.
[0086] The detection method is the same as in Example 2, and the results are shown in Table 7:
[0087] Table 7 Physical properties and flexural strength of foam ceramics
[0088]
[0089] Example 8
[0090] In this embodiment, a method for preparing high-strength foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0091] Except for the sintering system in step (3) (heating from room temperature to 1240° C., heating rate of 3° C. / min, keeping at this temperature for 20 min, and then cooling), the remaining steps are the same as those in Example 7. The results are shown in Table 8:
[0092] Table 8 Physical properties and flexural strength of foam ceramics
[0093]
[0094] Example 9
[0095] In this embodiment, a method for preparing high-strength foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0096] Except for the sintering system in step (3) (heating from room temperature to 1250° C., heating rate of 2° C. / min, keeping temperature for 40 min, and then cooling), the remaining steps are the same as those in Example 7. The results are shown in Table 9:
[0097] Table 9 Physical properties and flexural strength of foam ceramics
[0098]
[0099] Example 10
[0100] In this embodiment, a method for preparing high-strength foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0101] (1) First, the fly ash from the waste incineration in Guangxi was pretreated by washing to reduce its chloride ion content. In the experiment, 100g of dry waste incineration fly ash and 250ml of deionized water were weighed and added to a 500ml beaker (liquid-solid ratio of 2.5:1). A magnetic rotor was added and magnetic stirring was performed for 30min. The solid-liquid separation was performed using "qualitative filter paper + sand core filter device + vacuum pump". Deionized water was added and filtered until the filtrate was pure. The filtrate was then dried and weighed (dried at 105℃ for 12h). EDX was used to detect the content of each element in the fly ash before and after washing to verify the removal effect of chloride ions (ideal effect: the chloride ion content in the fly ash after washing is less than 0.1%).
[0102] (2) Then the washed Guangxi fly ash, kaolin and waste glass powder are mixed in a ratio of 2:2:1, and an appropriate amount of foaming agent silicon carbide is added to form a mixture; in the mixture, the content of SiO2 is 47.47wt%, the content of Al2O3 is 19.43wt%, the content of CaO is 17.57wt%, the content of SO3 is 5.48wt%, the content of MgO is 3.40wt%, the content of Fe2O3 is 1.95wt%, the content of Na2O is 1.07wt%, the content of SiC is 1wt%, the content of K2O is 0.56wt%, the content of TiO2 is 0.55wt%, the content of P2O5 is 0.50wt%, the content of MnO is 0.08wt%, and the remainder is impurities, totaling 100%; ball milling is carried out in a fast grinding mill for 8h (the ball-to-water ratio is 2:1:0.8), and after ball milling, it is dried at 105°C for 12h and sieved through 100 mesh.
[0103] (3) Finally, the required amount of the mixed material is weighed and pressed into a sheet (from 10 MPa until the pressure no longer decreases), placed in a corundum crucible, and sintered in a resistance furnace according to a prescribed firing schedule (heating from room temperature to 1145°C, heating rate of 3°C / min, keeping warm for 60 min, and then cooling) to obtain a foam ceramic product;
[0104] With reference to [national standard] GBT6569-2006 "Test method for bending strength of fine ceramics" and [national standard] JCT647-2005 "Foam ceramic insulation products", a microcomputer-controlled electronic universal testing machine was used with a sample size of 3*4*40mm, a loading speed of 0.5mm / min, and a span of 30mm to test and compare its bending strength.
[0105] With reference to [national standard] GBT1966-1996 "Test method for apparent porosity and bulk density of porous ceramics", [national standard] HJ1222-2021 "Solid waste-Determination of moisture and dry matter content-Gravimetric method", and HJT766-2015 "Solid waste-Leaching toxicity leaching method-sulfuric acid and nitric acid method", the Archimedes drainage method was used to test its various physical properties, and the flame atomic absorption spectrophotometer method was used to test its heavy metal leaching concentration. The results are shown in Table 10:
[0106] Table 10 Physical properties, flexural strength and heavy metal ion leaching concentration of foam ceramics
[0107]
[0108] Embodiment 11
[0109] In this embodiment, a method for preparing high-strength foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0110] (1) First, the waste incineration fly ash was pretreated by washing to reduce its chloride ion content. In the experiment, 100g of dry waste incineration fly ash and 250ml of deionized water were weighed and added into a 500ml beaker (liquid-solid ratio was 2.5:1). A magnetic rotor was added and magnetic stirring was performed for 30min. The solid-liquid separation was performed using "qualitative filter paper + sand core filter device + vacuum pump". Deionized water was added and filtered until the filtrate was pure. The filtrate was then dried and weighed (dried at 105℃ for 12h). EDX was used to detect the content of each element in the fly ash before and after washing to verify the removal effect of chloride ions (ideal effect: the chloride ion content in the fly ash after washing is less than 0.1%).
[0111] (2) Then the washed Guangxi fly ash, kaolin and waste glass powder are mixed in a ratio of 2:2:1, and an appropriate amount of foaming agent silicon carbide is added to form a mixture; in the mixture, the content of SiO2 is 47.47wt%, the content of Al2O3 is 19.43wt%, the content of CaO is 17.57wt%, the content of SO3 is 5.48wt%, the content of MgO is 3.40wt%, the content of Fe2O3 is 1.95wt%, the content of Na2O is 1.07wt%, the content of SiC is 1wt%, the content of K2O is 0.56wt%, the content of TiO2 is 0.55wt%, the content of P2O5 is 0.50wt%, the content of MnO is 0.08wt%, and the remainder is impurities, totaling 100%; ball milling is carried out in a fast grinding mill for 8h (the ball-to-water ratio is 2:1:0.8), and after ball milling, it is dried at 105°C for 12h and sieved through 100 mesh.
[0112] (3) Finally, the required amount of the mixed material is weighed and pressed into a sheet (from 10 MPa until the pressure no longer decreases), placed in a corundum crucible, and sintered in a resistance furnace according to the established firing schedule (heating from room temperature to 1145°C at a heating rate of 2°C / min, keeping warm for 20 min, and then cooling) to obtain a foam ceramic product.
[0113] With reference to [national standard] GBT6569-2006 "Test method for bending strength of fine ceramics" and [national standard] JCT647-2005 "Foam ceramic insulation products", a microcomputer-controlled electronic universal testing machine was used with a sample size of 3*4*40mm, a loading speed of 0.5mm / min, and a span of 30mm to test and compare its bending strength.
[0114] Referring to [national standard] GBT1966-1996 "Test method for apparent porosity and bulk density of porous ceramics", the Archimedes drainage method was used to test its various physical properties. The results are shown in Table 11:
[0115] Table 11 Physical properties, flexural strength and heavy metal ion leaching concentration of foam ceramics
[0116]
[0117] Example 12
[0118] In this embodiment, a method for preparing high-strength foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0119] Except for the sintering system in step (3) (heating from room temperature to 1145° C., heating rate of 4° C. / min, keeping at this temperature for 40 min, and then cooling), the remaining steps are the same as those in Example 11. The results are shown in Table 12:
[0120] Table 12 Physical properties, flexural strength and heavy metal ion leaching concentration of foam ceramics
[0121]
[0122] Embodiment 13
[0123] In this embodiment, a method for preparing high-strength foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0124] Except for the sintering system in step (3) (heating from room temperature to 1150° C., heating rate of 4° C. / min, keeping at this temperature for 20 min, and then cooling), the remaining steps are the same as those in Example 11. The results are shown in Table 13:
[0125] Table 13 Physical properties, flexural strength and heavy metal ion leaching concentration of foam ceramics
[0126]
[0127] Embodiment 14
[0128] In this embodiment, a method for preparing high-strength foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0129] Except for the sintering system in step (3) (heating from room temperature to 1150° C., heating rate of 3° C. / min, keeping at this temperature for 40 min, and then cooling), the remaining steps are the same as those in Example 11. The results are shown in Table 14:
[0130] Table 14 Physical properties, flexural strength and heavy metal ion leaching concentration of foam ceramics
[0131]
[0132] Embodiment 15
[0133] In this embodiment, a method for preparing high-strength foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0134] Except for the sintering system in step (3) (heating from room temperature to 1150° C., heating rate of 2° C. / min, keeping at this temperature for 60 min, and then cooling), the remaining steps are the same as those in Example 11. The results are shown in Table 15:
[0135] Table 15 Physical properties, flexural strength and heavy metal ion leaching concentration of foam ceramics
[0136]
[0137] Example 16
[0138] In this embodiment, a method for preparing high-strength foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0139] Except for the sintering system in step (3) (heating from room temperature to 1155° C., heating rate of 3° C. / min, keeping at this temperature for 20 min, and then cooling), the remaining steps are the same as those in Example 11. The results are shown in Table 16:
[0140] Table 16 Physical properties, flexural strength and heavy metal ion leaching concentration of foam ceramics
[0141]
[0142] Embodiment 17
[0143] In this embodiment, a method for preparing high-strength foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0144] Except for the sintering system in step (3) (heating from room temperature to 1155° C., heating rate of 2° C. / min, keeping at this temperature for 40 min, and then cooling), the remaining steps are the same as those in Example 11. The results are shown in Table 17:
[0145] Table 17 Physical properties, flexural strength and heavy metal ion leaching concentration of foam ceramics
[0146]
[0147] Embodiment 18
[0148] In this embodiment, a method for preparing high-strength foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0149] Except for the sintering system in step (3) (heating from room temperature to 1155° C., heating rate of 4° C. / min, keeping at this temperature for 60 min, and then cooling), the remaining steps are the same as those in Example 11. The results are shown in Table 18:
[0150] Table 18 Physical properties, flexural strength and heavy metal ion leaching concentration of foam ceramics
[0151]
[0152] The structure and performance of the samples prepared by the above typical implementation process are as follows:
[0153] Figure 1 The XRD spectra and physical images of Guangdong fly ash, Guangxi fly ash, kaolin, quartz, and waste glass powder in Example 1 and Example 10 are as follows: (a1) Guangdong fly ash; (a2) Guangxi fly ash; (b) kaolin; (c1) quartz; (c2) waste glass powder; Figure 2 The XRD spectra and physical images of the mixed materials and foam ceramics in Example 1 and Example 10, wherein (d1) contains the mixed material of Guangdong fly ash; (d2) contains the mixed material of Guangxi fly ash; (e1) contains the foam ceramics of Guangdong fly ash; (e2) contains the foam ceramics of Guangxi fly ash. Figure 1 and Figure 2 From the XRD images, we can see that the components of fly ash and mixed materials are relatively complex, kaolin, quartz and waste glass powder are relatively pure, and the main crystal phases in foam ceramics are calcium feldspar and calcium silicate.
[0154] Figure 3 These are the SEM images and pore size distribution diagrams of different areas of the Guangdong fly ash foam ceramics in Example 1, where (a), (b), (c) and (d) are SEM images of different positions, respectively, and (e) is a pore size distribution diagram. It can be seen that the pores are evenly distributed, mostly single pores, with very few connecting pores, and the pore diameter is mainly distributed at 284 μm.
[0155] Figure 4 The SEM images and pore size distribution diagrams of different areas of the foam ceramics containing Guangxi fly ash in Example 10: (a), (b), (c) and (d) are SEM images of different positions, respectively, and (e) is a pore size distribution diagram. It can be seen that the pores are evenly distributed, mostly single holes, with very few connecting holes, and the pore diameter is mainly distributed at 192μm.
[0156] Figure 5 (a) is the SEM image of the foam ceramic containing Guangdong fly ash in Example 1, (b) is the EDS spectrum of the foam ceramic containing Guangdong fly ash in Example 1, and (c) is the distribution diagram of each element in (a). From the figure, we can see the EDS spectra corresponding to the four elements O, Si, Al, and Ca, and the distribution of the four elements is relatively uniform.
[0157] Figure 6(a) is the EDS spectrum of the foam ceramic containing Guangxi fly ash in Example 10, (b) is the EDS spectrum of the foam ceramic containing Guangxi fly ash in Example 10, and (c) is the distribution diagram of each element in (a). From the figure, we can see the EDS spectra corresponding to the four elements O, Si, Al, and Ca, and the distribution of the four elements is relatively uniform.
[0158] The implementation results show that the heavy metal ion leaching concentration of the foam ceramic prepared by the method of the present invention meets the national standard requirements, and the flexural strength far exceeds the national standard requirements. It not only realizes waste utilization and provides a new way for the harmless treatment of fly ash from the incineration of domestic waste, but also turns waste into treasure and broadens the resource application field of fly ash from the incineration of domestic waste.
[0159] Comparative Example 1
[0160] In this comparative example, a method for preparing foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0161] (1) First, the fly ash from the waste incineration in Guangxi was pretreated by washing to reduce its chloride ion content. In the experiment, 100g of dry waste incineration fly ash and 250ml of deionized water were weighed and added to a 500ml beaker (liquid-solid ratio of 2.5:1). A magnetic rotor was added and magnetic stirring was performed for 30min. The solid-liquid separation was performed using "qualitative filter paper + sand core filter device + vacuum pump". Deionized water was added and filtered until the filtrate was pure. The filtrate was then dried and weighed (dried at 105℃ for 12h). EDX was used to detect the content of each element in the fly ash before and after washing to verify the removal effect of chloride ions (ideal effect: the chloride ion content in the fly ash after washing is less than 0.1%).
[0162] (2) Then the washed Guangxi fly ash, kaolin and waste glass powder are mixed in a ratio of 5:4:11, and an appropriate amount of foaming agent silicon carbide is added to form a mixture; in the mixture, the content of SiO2 is 65.07wt%, the content of Al2O3 is 11.38wt%, the content of CaO is 11.08wt%, the content of SO3 is 3.51wt%, the content of Na2O is 2.94wt%, the content of Mg is 2.13wt%, the content of Fe2O3 is 1.22wt%, the content of SiC is 1wt%, the content of P2O5 is 0.38wt%, the content of K2O is 0.36wt%, the content of TiO2 is 0.35wt%, the content of MnO is 0.05wt%, and the remainder is impurities, totaling 100%; ball milling is carried out in a fast grinding mill for 8h (the ball-to-water ratio is 2:1:0.8), and after ball milling, it is dried at 105°C for 12h and sieved through 100 mesh.
[0163] (3) Finally, the required amount of the mixed material is weighed and pressed into a sheet (from 10 MPa until the pressure no longer decreases), and a corundum pad is placed on the sheet. The sheet is sintered in a resistance furnace according to the specified firing schedule (heating from room temperature to 1145°C at a heating rate of 3°C / min, keeping the temperature for 60 min, and then cooling) to obtain a foam ceramic product.
[0164] Compared with Example 10, only the formula ratio of the raw materials is changed, the SiO2 content exceeds the control range of 40wt% to 60wt%, and the foam glass is Figure 7 As shown, Figure 7 In the figure, (a) is a physical picture of the foam glass of comparative example 1, and (b) is a physical picture of the cross section of the foam glass of comparative example 1.
[0165] Depend on Figure 7 It can be seen that the SiO2 content in the formula raw materials should be controlled at 40wt% to 60wt%. If it exceeds this range, foam ceramics cannot be sintered within the determined firing system. This is because the increase in SiO2 content will lead to an increase in the sintering temperature, and the preparation of foam ceramic products requires more energy, which is not conducive to energy conservation and emission reduction. At the same time, the fly ash utilization rate of this ratio formula is low, and the waste utilization effect is average.
[0166] Comparative Example 2
[0167] In this comparative example, a method for preparing foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0168] (1) First, the fly ash from the waste incineration in Guangxi was pretreated by washing to reduce its chloride ion content. In the experiment, 100g of dry waste incineration fly ash and 250ml of deionized water were weighed and added to a 500ml beaker (liquid-solid ratio of 2.5:1). A magnetic rotor was added and magnetic stirring was performed for 30min. The solid-liquid separation was performed using "qualitative filter paper + sand core filter device + vacuum pump". Deionized water was added and filtered until the filtrate was pure. The filtrate was then dried and weighed (dried at 105℃ for 12h). EDX was used to detect the content of each element in the fly ash before and after washing to verify the removal effect of chloride ions (ideal effect: the chloride ion content in the fly ash after washing is less than 0.1%).
[0169] (2) Then the washed Guangxi fly ash, kaolin and waste glass powder are mixed in a ratio of 3:6:1, and an appropriate amount of foaming agent silicon carbide is added to form a mixture; in the mixture, the content of SiO2 is 48.18wt%, the content of Al2O3 is 26.76wt%, the content of CaO is 13.16wt%, the content of SO3 is 4.12wt%, the content of MgO is 2.55wt%, the content of Fe2O3 is 1.67wt%, the content of SiC is 1wt%, the content of K2O is 0.59wt%, the content of Na2O is 0.53wt%, the content of TiO2 is 0.42wt%, the content of P2O5 is 0.37wt%, the content of MnO is 0.06wt%, and the remainder is impurities, totaling 100%; ball milling is carried out in a fast grinding mill for 8h (the ball-to-water ratio is 2:1:0.8), and after ball milling, it is dried at 105°C for 12h and sieved through 100 mesh.
[0170] (3) Finally, the required amount of the mixed material is weighed and pressed into a sheet (from 10 MPa until the pressure no longer decreases), and a corundum pad is placed on the sheet. The sheet is sintered in a resistance furnace according to the specified firing schedule (heating from room temperature to 1145°C at a heating rate of 3°C / min, keeping the temperature for 60 min, and then cooling) to obtain a foam ceramic product.
[0171] Compared with Example 10, only the formula ratio of the raw materials is changed, the Al2O3 content exceeds the control range of 10wt% to 20wt%, and the foam ceramics that are not sintered sufficiently are Figure 8 As shown, Figure 8 (a) is the actual foam ceramic of the incomplete sintering of Comparative Example 2 Figure 1 , (b) is the actual foam ceramic of the incomplete sintering of Comparative Example 2 Figure 2 .
[0172] Depend on Figure 8 It can be seen that the content of Al2O3 in the formula raw materials should be controlled at 10wt% to 25wt%. If it exceeds this range, foam ceramics cannot be sintered within the determined firing system. This is because the increase in Al2O3 content will cause the softening temperature of the sample to increase, thereby leading to an increase in the sintering temperature. The preparation of foam ceramic products requires more energy, which is not conducive to energy conservation and emission reduction. At the same time, the fly ash utilization rate of this ratio formula is low, and the waste utilization effect is average.
[0173] Comparative Example 3
[0174] In this comparative example, a method for preparing foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0175] (1) First, the fly ash from the waste incineration in Guangxi was pretreated by washing to reduce its chloride ion content. In the experiment, 100g of dry waste incineration fly ash and 250ml of deionized water were weighed and added to a 500ml beaker (liquid-solid ratio of 2.5:1). A magnetic rotor was added and magnetic stirring was performed for 30min. The solid-liquid separation was performed using "qualitative filter paper + sand core filter device + vacuum pump". Deionized water was added and filtered until the filtrate was pure. The filtrate was then dried and weighed (dried at 105℃ for 12h). EDX was used to detect the content of each element in the fly ash before and after washing to verify the removal effect of chloride ions (ideal effect: the chloride ion content in the fly ash after washing is less than 0.1%).
[0176] (2) Then the washed Guangxi fly ash, kaolin and waste glass powder are mixed in a ratio of 11:4:5, and an appropriate amount of foaming agent silicon carbide is added to form a mixture; in the mixture, the content of SiO2 is 43.10wt%, the content of CaO is 24.15wt%, the content of Al2O3 is 12.73wt%, the content of SO3 is 7.51wt%, the content of MgO is 4.68wt%, the content of Fe2O3 is 2.44wt%, the content of Na2O is 1.34wt%, the content of SiC is 1wt%, the content of TiO2 is 0.74wt%, the content of P2O5 is 0.68wt%, the content of K2O is 0.56wt%, the content of MnO is 0.10wt%, and the remainder is impurities, totaling 100%; ball milling is carried out in a fast grinding mill for 8h (the ball-to-water ratio is 2:1:0.8), and after ball milling, it is dried at 105°C for 12h and sieved through 100 mesh.
[0177] (3) Finally, the required amount of the mixed material is weighed and pressed into a sheet (from 10 MPa until the pressure no longer decreases), and a corundum pad is placed on the sheet. The sheet is sintered in a resistance furnace according to the specified firing schedule (heating from room temperature to 1145°C at a heating rate of 3°C / min, keeping the temperature for 60 min, and then cooling) to obtain a foam ceramic product.
[0178] Compared with Example 10, only the formula ratio of the raw materials is changed, the CaO content exceeds the control range of 10wt% to 20wt%, and the glass ceramics such as Fig. 9 As shown, Fig. 9 (a) is the actual glass ceramic of Comparative Example 3 Figure 1 , (b) is the actual glass ceramic of Comparative Example 3 Figure 2 .
[0179] Depend on Fig. 9It can be seen that the CaO content in the formula raw materials should be controlled at 10wt% to 20wt%. If it exceeds this range, foam ceramics cannot be sintered within the specified sintering system. This is because CaO can be used as a sintering aid. Excessive content will significantly reduce the sintering temperature, making it difficult for the foaming agent SiC to function.
[0180] Comparative Example 4
[0181] In this comparative example, a method for preparing foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash comprises the following steps:
[0182] (1) First, the fly ash from the waste incineration in Guangxi was pretreated by washing to reduce its chloride ion content. In the experiment, 100g of dry waste incineration fly ash and 250ml of deionized water were weighed and added to a 500ml beaker (liquid-solid ratio of 2.5:1). A magnetic rotor was added and magnetic stirring was performed for 30min. The solid-liquid separation was performed using "qualitative filter paper + sand core filter device + vacuum pump". Deionized water was added and filtered until the filtrate was pure. The filtrate was then dried and weighed (dried at 105℃ for 12h). EDX was used to detect the content of each element in the fly ash before and after washing to verify the removal effect of chloride ions (ideal effect: the chloride ion content in the fly ash after washing is less than 0.1%).
[0183] (2) Then the washed Guangxi fly ash, kaolin and waste glass powder are mixed in a ratio of 2:2:1, and an appropriate amount of foaming agent silicon carbide is added to form a mixture; in the mixture, the content of SiO2 is 46.99wt%, the content of Al2O3 is 19.43wt%, the content of CaO is 17.39wt%, the content of SO3 is 5.42wt%, the content of MgO is 3.37wt%, the content of Fe2O3 is 1.93wt%, the content of SiC is 2wt%, the content of Na2O is 1.06wt%, the content of K2O is 0.56wt%, the content of TiO2 is 0.54wt%, the content of P2O5 is 0.50wt%, the content of MnO is 0.08wt%, and the remainder is impurities, totaling 100%; ball milling is carried out in a fast grinding mill for 8h (the ball-to-water ratio is 2:1:0.8), and after ball milling, it is dried at 105°C for 12h and sieved through 100 mesh.
[0184] (3) Finally, the required amount of the mixed material is weighed and pressed into a sheet (from 10 MPa until the pressure no longer decreases), and a corundum pad is placed on the sheet. The sheet is sintered in a resistance furnace according to the specified firing schedule (heating from room temperature to 1145°C at a heating rate of 3°C / min, keeping the temperature for 60 min, and then cooling) to obtain a foam ceramic product.
[0185] Compared with Example 10, only the foaming agent content is increased to 2wt%, exceeding the SiC content control range of 0.2wt% to 1wt%. Fig.10 As shown, Fig.10 In the figure, (a) is a physical picture of the foam ceramic of comparative example 4, and (b) is a physical picture of the cross section of the foam ceramic of comparative example 4.
[0186] Depend on Fig.10 It can be seen that the content of foaming agent SiC in the formula raw materials should be controlled at 0.2wt~1wt%. If it exceeds this range, the foaming effect of foam ceramics is extremely poor. This is because the excessive content of the foaming agent aggregates, resulting in the appearance of a large number of large holes, making it difficult to process and perform performance tests, and cannot be applied to production practice.
[0187] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing foam ceramics based on high-calcium and low-silicon domestic waste incineration fly ash, characterized in that: The following steps are involved: Washing high-calcium and low-silicon domestic waste incineration fly ash to reduce the chloride ion content; the high-calcium and low-silicon domestic waste incineration fly ash contains 30wt% to 45wt% CaO and 15wt% to 25wt% SiO2; Washed fly ash, kaolin and quartz or waste glass powder are used as raw materials, silicon carbide is used as a foaming agent, mixed and ball-milled, and after ball-milling, dried and sieved to prepare a mixed material; The mixed material is pressed into tablets, and then sintered to obtain foam ceramics; The mixture contains the following components: 40wt% to 60wt% of SiO2, 10wt% to 25wt% of Al2O3, 10wt% to 20wt% of CaO, and 0.2wt% to 1.0wt% of silicon carbide.
2. The method according to claim 1, characterized in that The domestic waste incineration fly ash consists of the following components composition: CaO: 30wt% ~ 35wt%, SiO2: 20wt% ~ 25wt%, Al2O3: 10wt% ~ 15wt%, SO3: 10wt% ~ 15wt%, Fe2O3: 5wt% ~ 10wt%, MgO: 5wt% ~ 10wt%, TiO2: 1wt% ~ 2wt%, K2O: 1wt% ~ 2wt%, P2O5: 0.5wt% ~ 1.5wt%, MnO: 0.1wt% ~ 0.5wt%, the remainder is impurities, totaling 100%.
3. The method according to claim 2, characterized in that The sintering procedure is: heating from room temperature to 1230°C ~ 1250°C, with a heating rate of 2°C / min ~ 4°C / min, keeping warm for 20min ~ 60min, and then cooling down.
4. The method according to claim 1, characterized in that: The domestic waste incineration fly ash is composed of the following components: CaO: 40wt% ~ 45wt%, SiO2: 15wt% ~ 20wt%, SO3: 10wt% ~ 15wt%, Al2O3: 5wt% ~ 10wt%, MgO: 5wt% ~ 10wt%, Fe2O3: 1wt% ~ 5wt%, TiO2: 1wt% ~ 2wt%, P2O5: 1wt% ~ 2wt%, K2O: 0.1wt% ~ 1wt%, MnO: 0.1wt% ~ 0.5wt%, the remainder is impurities, totaling 100%.
5. The method according to claim 4, characterized in that The sintering procedure is: heating from room temperature to 1145°C ~ 1155°C, with a heating rate of 2°C / min ~ 4°C / min, keeping warm for 20min ~ 60min, and then cooling down.
6. The method according to claim 1, characterized in that Kaolin is composed of the following ingredients: SiO2: 55wt%~60wt%, Al2O3: 40wt%~45wt%, Fe2O3: 0.1wt%~1wt%, K2O: 0.1wt%~1wt%, TiO2: 0.01wt%~0.1wt%, BaO: 0.01wt%~0.1wt%, MnO: 0.01wt%~0.1wt%, SO3: 0.01wt%~0.1wt%, the remainder is impurities, totaling 100%.
7. The method according to claim 1, characterized in that Quartz is composed of the following components: SiO2: 99.00wt%~99.80wt%, Al2O3: 0.1wt%~1wt%, Fe2O3: 0.01wt%~0.1wt%, CaO: 0.01wt%~0.1wt%, SO3: 0.01wt%~0.1wt%, totaling 100%.
8. The method according to claim 1, characterized in that Waste glass powder consists of the following components: SiO2: 90wt% ~ 95wt%, Na2O: 5wt% ~ 10wt%, Al2O3: 1wt% ~ 5wt%, CaO: 0.1wt% ~ 0.5wt%, K2O: 0.1wt% ~ 0.5wt%, P2O5: 0.1wt% ~ 0.5wt%, SO3: 0.1wt% ~ 0.5wt%, Fe2O3: 0.01wt% ~ 0.1wt%, TiO2: 0.01wt% ~ 0.1wt%, the remainder is impurities, totaling 100%.
9. The method according to claim 1, characterized in that: The mass ratio of the washed fly ash, kaolin, quartz or waste glass powder is 2:2:
1.
10. The method according to claim 1, characterized in that The particle size of the raw materials does not exceed 100 mesh, the particle size of silicon carbide is ≤30 μm, the mixed material is ball-milled and dried, and then passed through a 100 mesh sieve.
Citation Information
Patent Citations
Monoclinic barium feldspar ceramic with low thermal expansion coefficient and preparation method
CN110483029A
Formula and method for producing foamed ceramic by taking waste incineration fly ash as main body
CN113402257A
Foaming ceramic material based on low-silicon high-calcium iron tailings and preparation method thereof
CN117263650A
Method for preparing porous ceramic by sintering household garbage incineration fly ash
CN117550912A
Ceramic foamed body and its manufacturing method
JP2002321988A